The Stigma of COVID-19 on the Workers of PT. Pertamina EP Asset 5 Sangatta Field - Permana, Lies; Rahmatullah, Kukuh; Hasmawati, Hasmawati; Wiranto, Agus (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: COVID-19 in Indonesia spreads very quickly, including in-company areas or workplaces. Workplace clusters are the most common cluster at East Kalimantan. As a region with many workplaces, both offices and industries, East Kalimantan is bound to have a large number of office clusters. Moreover, most of the workers in East Kalimantan are migrants from outside the region, which causes the spread of the coronavirus to the workplace even more widely. This also happened to PT. Pertamina EP Asset 5 Sangatta Field, where some of the workers are workers from outside the East Kutai area. With the presence of several workers who have tested positive for COVID-19, it is a frightening thing for others, especially other workers. Negative stigma may occur among workers in this company.Method: The research design used in this study is cross-sectional since this study wants to know the knowledge and attitudes towards the stigma of COVID-19, which is measured at the same time. This research was conducted from November - December 2020. The population in this study were all workers who worked at PT Pertamina EP Sangatta Field, in total of 238 people.Results: It shows that attitude relates to stigma COVID-19 among workers (P-Value = <0.001), although knowledge has nothing to do with stigma. The importance of accurate information is expected to reduce stigma in society. Discrimination and fear regarding COVID-19 must be minimized in order to gain acceptance by the community.